Traitement des eaux usées dans la station d’épuration de Cap Falcon-Oran, diagnostic et perspectives - BENNIA, Yamna (My University, 2020)
The discharge of untreated wastewater causes degradation of water quality and the environment; these contain many non-eliminated organic pollutants. As part of the preservation of public health and sustainable development, STEP-Cap Falcon treats its effluents by activated sludge at low load. The treated wastewater is a source of nutrients allowing a saving of fertilizer. The objective of this work is to reduce the levels of pollutants present in wastewater to values respecting national and international standards. A wastewater reuse project remains a water use project. The fact that this water is used only provides technical corrections; the reason why a daily monitoring of their physicochemical quality at the entry and the exit of the STEP (BOD5, COD, MES nitrogen, total phosphor) must be realized. The results of the analyzes carried out showed a good functioning of the station, a good efficiency in purifying suspended matter (MES) and a rate of abatement at an acceptable level of the chemical oxygen demand (COD) and the biological oxygen demand (BOD5), and the removal of nitrogen and phosphorus by the activated sludge technique is effective..
Keywords: purified wastewater; MES; BOD5; COD; Nitrogen; total phosphor STEP; Cap-Falcon.